Kajian Sandal Upanat Borobudur: Integrasi Desain, Materialitas, Ergonomi, dan Keberlanjutan dalam Konteks Warisan Budaya - Sri Utami (Dampeng: Journal of Art, Heritage and Culture, 2026)
This study examines the Upanat sandals of Borobudur as part of cultural heritage through an interdisciplinary approach encompassing design, materiality, ergonomics, and sustainability. It aims to understand the historical and cultural values of Upanat sandals while exploring their potential for contemporary design development relevant to present needs. The methods include literature review, visual observation of Borobudur reliefs, and comparative analysis with modern sandal products. The findings indicate that Upanat sandals feature a simple yet functional design, with opportunities for adaptation using environmentally friendly materials and improved ergonomic aspects. Integrating traditional values with modern design approaches enables the creation of products that are not only aesthetically appealing but also sustainable and contextually relevant. In addition, this study highlights opportunities for culture-based design innovation in supporting creative industries and sustainable economic development. This research contributes to the advancement of culture-based design and reinforces the role of cultural heritage as a source of innovation in the creative industries. [Penelitian ini mengkaji Sandal Upanat Borobudur sebagai bagian dari warisan budaya melalui pendekatan interdisipliner yang mencakup desain, materialitas, ergonomi, dan keberlanjutan. Studi ini bertujuan untuk memahami nilai historis dan kultural sandal Upanat sekaligus mengeksplorasi potensinya dalam pengembangan desain kontemporer yang relevan dengan kebutuhan masa kini. Metode yang digunakan meliputi studi literatur, observasi visual terhadap relief Borobudur, serta analisis komparatif terhadap produk sandal modern. Hasil penelitian menunjukkan bahwa sandal Upanat memiliki karakter desain yang sederhana namun fungsional, dengan potensi adaptasi material yang lebih ramah lingkungan dan peningkatan aspek ergonomi. Integrasi nilai tradisi dengan pendekatan desain modern memungkinkan terciptanya produk yang tidak hanya estetis, tetapi juga berkelanjutan dan kontekstual. Selain itu, kajian ini juga menyoroti peluang inovasi desain berbasis budaya lokal dalam mendukung industri kreatif dan ekonomi berkelanjutan. Penelitian ini berkontribusi pada pengembangan desain berbasis budaya serta memperkuat peran warisan budaya sebagai sumber inspirasi inovasi dalam industri kreatif.]